Introduction to non-linear systems / J. Berry. - Berry, John, 1947- (Modular mathematics series, 1996)
This book provides a basic course in non-linear differential and difference equations - the basis ofchaos. It will follow the series style, including numerous tutorial problems, exercises and worked examples.